Nanosilicon stabilized with ligands: Effect of high‐energy electron beam on luminescent properties. (28th June 2020) - Aslanov, Leonid A.; Zaytsev, Vladimir B.; Zakharov, Valery N.; Kudryavtsev, Igor K.; Senyavin, Vladimir M.; Lagov, Petr B.; Pavlov, Yuri S.
Abstract : Silicon nanopowders with nitrogen heterocyclic carbene (NHC) and butyl as stabilizing ligands were synthesized by bottom up chemical methods. Transmission electron microscopy (TEM) was used to obtain nanoparticle size distribution with 1.8–2.5 mm average diameter. Optical characteristics (photoluminescence and infrared (IR) absorption spectra) of samples were investigated as fabricated and on different steps of irradiation by high‐energy 7‐MeV electrons. The photoluminescence (PL) spectral changes are slightly different for two cases, but in general, we can see a decrease in luminescence amplitude with fluence growth up to 1.2·10 16 cm −2, mainly for NHC stabilized nanosilicon. Main mechanisms of radiation‐induced changes in nanosilicon sample optical properties are discussed by the joint use of PL and IR spectra analysis.